Factors influencing streaming to General Practitioners in emergency departments: A qualitative study. (August 2021) - Anderson, Helen; Scantlebury, Arabella; Leggett, Heather; Brant, Heather; Salisbury, Chris; Benger, Jonathan; Adamson, Joy
Abstract: Background: Emergency Department attendance is increasing internationally, of which a significant proportion could be managed in general practice. In England, policies backed by substantial capital funding require such patients attending Emergency Departments be directed or 'streamed' to General Practitioners working in or parallel to Emergency Departments. However, evidence for streaming is limited and the processes of streaming patients attending Emergency Departments to General Practitioners lacks exploration. Objectives: This paper explores streaming to General Practitioners in and alongside Emergency Departments at ten sites across England. It highlights positive streaming practice, as well as issues that may contribute to poor streaming practice, in order to inform future service improvement. Methods: A longitudinal qualitative study was conducted with data collected between October 2017 and December 2019 across 10 case study sites throughout England as part of a broader mixed methods study. 186 non-participant observations and 226 semi-structured interviews with 191 health professionals working in Emergency Departments or related General Practitioner Services were thematically analysed in relation to streaming processes and experiences. Results: Six interconnected themes influencing streaming were identified: implementing and maintaining structural support; developing and supporting streaming personnel; implementing workable and responsive streaming protocols; negotiating primary/secondary care boundaries; developing and maintaining interprofessional relationships and concerns for patient safety. Streaming was considered central to the success of General Practitioners in/parallel to Emergency Departments. The importance of the skills of streaming nurses in delivering an optimal and safety critical service was highlighted, as was the skillset of General Practitioners and interprofessional relationships between streamers and General Practitioners. There was no distinct streaming model or method associated with good streaming practice to General Practitioners in/alongside Emergency Departments, instead factors for success were identified and key recommendations suggested. 'Inappropriate' streaming was identified as a problem, where patients streamed to General Practitioners in or parallel to Emergency Departments required Emergency Department management, or patients suitable for General Practitioner care were kept in the Emergency Department. Conclusion: Despite adopting differing methods, commonalities across case sites in the delivery of good streaming practice were identified, leading to identification of key recommendations which may inform development of streaming services. Study Registration: ISRCTN51780222. Tweetable abstract : Workplace culture and the skillset of streamers and General Practitioners is crucial to streaming of patients to General Practitioners in Emergency Departments